2022
DOI: 10.3390/ijms23084284
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy as a Source of Nucleic Acid Biomarkers in the Diagnosis and Management of Lynch Syndrome

Abstract: Lynch syndrome (LS) is an autosomal dominant inherited cancer predisposition disorder, which may manifest as colorectal cancer (CRC), endometrial cancer (EC) or other malignancies of the gastrointestinal and genitourinary tract as well as the skin and brain. Its genetic cause is a defect in one of the four key DNA mismatch repair (MMR) loci. Testing of patients at risk is currently based on the absence of MMR protein staining and detection of mutations in cancer tissue and the germline, microsatellite instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…Over the past decade, much effort has been devoted to the development of non-invasive approaches for cancer diagnosis and monitoring to replace the conventional invasive techniques [ 129 , 130 , 131 ]. Although associations between TL and cancer risk or prognosis have been extensively investigated in tumor tissues [ 69 ], cell-free telomeric DNA (cf-telDNA) remains poorly explored despite its potential suitability to become an informative genetic biomarker for many cancers ( Table 2 ).…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%
“…Over the past decade, much effort has been devoted to the development of non-invasive approaches for cancer diagnosis and monitoring to replace the conventional invasive techniques [ 129 , 130 , 131 ]. Although associations between TL and cancer risk or prognosis have been extensively investigated in tumor tissues [ 69 ], cell-free telomeric DNA (cf-telDNA) remains poorly explored despite its potential suitability to become an informative genetic biomarker for many cancers ( Table 2 ).…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%
“…The identification of potential cell-free DNA-based and RNA-based biomarkers extracted from liquid biopsy might have a future role in the diagnosis of Lynch syndrome and in combination with, or as an alternative to, colonoscopy. 90 However, these markers need to be confirmed and standardized, cost-efficient testing methods prior to clinical implementation need to be developed. 90 A recent study reported that cfDNA multi-omic analysis distinguishes MPNST from plexiform neurofibromas with high sensitivity, and cfDNA levels in NF1 significantly correlate with MPNST tumor burden.…”
Section: Clinical Utility Of Liquid Biopsies In Hereditary Cancermentioning
confidence: 99%
“… 90 However, these markers need to be confirmed and standardized, cost-efficient testing methods prior to clinical implementation need to be developed. 90 A recent study reported that cfDNA multi-omic analysis distinguishes MPNST from plexiform neurofibromas with high sensitivity, and cfDNA levels in NF1 significantly correlate with MPNST tumor burden. 91 By identifying distinctive pathways underlying MPNST pathogenesis, it this technique might allow clinicians to sub-classify MPNSTs to correlate with prognosis and develop personalized treatment plans.…”
Section: Clinical Utility Of Liquid Biopsies In Hereditary Cancermentioning
confidence: 99%
“…This replication error phenotype is considered to be a hallmark of a hereditary cancer-prone syndrome, increasing individual risk for various malignancies. It is called Lynch syndrome (LS) [ 10 ] and MSI occurs in approximately 90% of cases [ 11 , 12 ]. Tumours are conventionally classified according to the proportion of unstable STR markers into the following classes: (i) MSI-H (microsatellite instability-high), (ii) MSI-L (MSI-low) and (iii) MSS (microsatellite stable) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%